Computer complex for detection and evaluation of crisis situations in information sphere - Гізун, Андрій Іванович (Ukrainian Information Security Research Journal, 2016)
Today to ensure the effective information resources security it is needed not only to identify the crisis satiation, but also to identify and evaluate the level of information security threats, which were caused by it. Most of the known detection and prediction evaluation systems for crisis situations are based on the signature or comparator principles. Thus they can not be used in the fuzzy weakly-formalized environment. This creates obstacles for their functioning in real information systems. This problem is solved by using fuzzy logic application and expert approach. In this paper represented the basic architecture of a new structural solution: computer complex which consist of incidents / potential crises detection and situation criticality evaluation system. Complex architecture is represented as structural modules and blocks, which is associated by logically functional connections. Each system can be used separately and independently or together for the crisis situation management tasks in the information scope.